2010
DOI: 10.4021/gr2010.01.1333
|View full text |Cite
|
Sign up to set email alerts
|

Primary Pure Squamous Cell Carcinoma of the Duodenum: A Case Report

Abstract: Only two cases of squamous cell carcinoma of the duodenum have been reported in the literature. The author herein reports a case of squamous cell carcinoma of the duodenum. A 75-year-old man was admitted to our hospital because of nausea, vomiting, and weakness. An endoscopic examination revealed a duodenal tumor. The tumor was circumferential elevated one with duodenal obstruction, and located in the descending part near and distal to the ampulla of Vater. Imaging modalities also detected the duodenal tumor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 4 publications
1
15
0
1
Order By: Relevance
“…[1][2][3][4][5][6] By definition, primary SCC of the endometrium cannot have co-existing primary endometrial adenocarcinoma, connection with cervical squamous epithelium, or co-existing primary cervical SCC. [1][2][3][4][5][6] Primary endometrial SCC may arise in association with squamous metaplasia and dysplasia in the setting of pyometria 7,8 or ichthyosis uteri. [9][10][11] Rare cases of verrucous carcinoma of the endometrium have been also reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] By definition, primary SCC of the endometrium cannot have co-existing primary endometrial adenocarcinoma, connection with cervical squamous epithelium, or co-existing primary cervical SCC. [1][2][3][4][5][6] Primary endometrial SCC may arise in association with squamous metaplasia and dysplasia in the setting of pyometria 7,8 or ichthyosis uteri. [9][10][11] Rare cases of verrucous carcinoma of the endometrium have been also reported.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 A high Ki-67 in the differential diagnosis for these patients, despite its rarity. The exact pathogenesis is unclear and diagnosis is based on strict pathological criteria.…”
Section: Resultsmentioning
confidence: 99%
“…6,10 It is also essential to differentiate PESCC from endometrial SCC involvement based on the following strict pathological criteria recommended by Fluhmann: (1) no evidence of a coexisting endometrial adenocarcinoma or primary cervical SCC; (2) no connection between the endometrial tumour and squamous epithelium of the cervix; or Sujata Jetley, Zeeba S. Jairajpuri, Mohammad J. Hassan, Garima Madaan and Reena Jain Online Case Report | e561 labelling index has also been reported, demonstrating the aggressive and malignant nature of the lesion. 18 Lee et al found a positive immunoreactivity for the cytokeratin 7, p63 and p16INK4a proteins, but not for cytokeratin 20 or the oestrogen and progesterone receptors. 6 As a prognostic indicator of PESCC, the role of these receptors is still uncertain; however, lack of oestrogen cannot be completely ruled out as an aetiological factor since most patients diagnosed with PESCC are postmenopausal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, [23] showed that expression for p53 can be seen in endometriod adenocarcinomas (~10%) cases.Our results positivity expression for p53 were higher significant in papillary serous than endometriod carcinomas. .However, [24] were explained that immunohistochemical positive for p53 [25] showed that in mucinous tumors p53 mutation was rarely.…”
Section: 4: P53 Expression and Intensity In Endometrial Cancer Accomentioning
confidence: 99%